Instrument Development and Validation of Social Commerce Success - Erne Suzila Kassim; Norol Hamiza Zamzuri; Abdul Kadir Othman (International Journal of Supply Chain Management, 2017)
This paper provides a discussion on social commerce and describes the development of an instrument to measure social commerce success. Based on the literature and findings of an exploratory study, a measurement was designed and validated. Five constructs were posited to be interrelated, which were process quality, communication quality, security and payment, service quality and social commerce loyalty. Using exploratory factor analysis, and confirmatory factor analysis, consistency between the data yielded by the scale were found. The model fit meets the CFA requirements and the values of composite reliability, AVE and discriminant validity surpassed the minimum values. It is concluded the instrument constitutes a unique and adequate measure of social commerce success.